عزل وتشخيص بكتريا من الأغذية الموجودة في الأسواق المحلية Enterobacter Sakazakii ودراسة تأثير كل من مضادات الحياة ودرجة الحرارة على نموها - شفيق مي حاتم (Al-Nahrain Journal of Science, 2010)
This research was performed to studyEnterobacter sakazakii which causes manydiseases. The bacteria was isolated fromdifferent local foods, and identified whendeveloped yellow pigmented colonies on TSAand oxidase positive.The bacteria were resistant to hightemperature up to 60°c but above thistemperature (65°c) the bacteria were killedafter 15 min incubation, also the bacteria wereresistant to low temperature until 8°c for 24hr. This bacteria were resistant to most of theantibiotics used in the study except: Nalidixicacid, Kanamycin, and riphampin.